Silver nanoparticles green synthesis: What is green and safe for science education? - Takala, Aleksi; Haatainen, Outi; Vuorio, Emmi; Pesonen, Reija (LUMAT-B: International Journal on Math, Science and Technology Education, 2023)
Nanoparticles are 1–100 nm in diameter and exhibit unique qualities that are different in comparison to the same elements on a larger scale. These properties make nanoparticles widely used in various industries and consumer products. However, silver nanoparticles are a cause for concern because they are biologically active and potentially toxic. In this paper, we present a safe green synthesis workshop for silver nanoparticles that aim to engage students to have discussions regarding chemistry in a safer manner based on green synthesis and green chemistry. A Likert scale questionnaire was produced and implemented, and the results (N=7) indicated positive but inconclusive results regarding interest and understanding of concepts. The revision of the workshop and the further study of the topic aims to better accomplish these tasks.